Evolutionary, structural and functional insights in nuclear organisation and nucleocytoplasmic transport in trypanosomes - Padilla-Mejia, Norma E; Field, Mark C (FEBS letters, 2023)
One of the remarkable features of eukaryotes is the nucleus, delimited by the nuclear envelope (NE), a complex structure and home to the nuclear lamina and nuclear pore complex (NPC). For decades, these structures were believed to be mainly architectural elements and, in the case of the NPC, simply facilitating nucleocytoplasmic trafficking. More recently, the critical roles of the lamina, NPC and other NE constituents in genome organisation, maintaining chromosomal domains and regulating gene expression have been recognised. Importantly, mutations in genes encoding lamina and NPC components lead to pathogenesis in humans, while pathogenic protozoa disrupt the progression of normal development and expression of pathogenesis-related genes. Here, we review features of the lamina and NPC across eukaryotes and discuss how these elements are structured in trypanosomes, protozoa of high medical and veterinary importance, highlighting lineage-specific and conserved aspects of nuclear organisation.
Keywords: aktivní transport - buněčné jádro; Humans; Nuclear Pore Complex Proteins; Nuclear Envelope; Nuclear Pore; evolutionary diversity; nuclear pore complex; trypanosoma; jaderný obal; nucleus; nuclear lamina; Active Transport, Cell Nucleus; Trypanosoma; komplex proteinů jaderného póru; lidé; jaderný pór